Review of the species in the Cyclocephala bicolor Laporte species group (Coleoptera: Scarabaeidae: Dynastinae) - Joly, Luis J. (Zootaxa, 2009)
The species in the Cyclocephala bicolor Laporte species group are revised. C. bicolor Laporte, C. bicolorata Endrödi, C. sarahae Ratcliffe, and C. dichroa Dechambre are redescribed, and C. anibali, sp. n. is described from Venezuela. The group is characterized and a key for identification of the species, drawings of the key characters, and distribution maps are presented.